PENGARUH FAKTOR PSIKOLOGI DAN SOSIAL BUDAYA TERHADAP KEPUTUSAN WISATAWAN BERWISATA DI TAMAN NASIONAL GUNUNG RINJANI - Ridha, Rasid (Jurnal Magister Manajemen, 2016)
This study aimed to analyze the influence of psychological factors and socio-cultural factors of the tourists traveled decision on Mount Rinjani National Park. Respondent was done by using purposive sampling using a questionnaire distributed to 100 respondents. The data analysis technique used is multiple linear regression analysis. Based on the analysis that has been done, it can be concluded that psychological factors and socio-cultural factors a significant and positive influence on the decision travelers traveled on Mount Rinjani National Park. This means that if psychological factors and socio-cultural factors improved by the manager of the Mount Rinjani National Park, can improve decision-traveled. While the dominant variable affecting traveled decision is socio-cultural factors. Keywords: Psychological Factors, Socio-Cultural Factors, and Decision Travelling.